Environmental Accounting Practices in Printing MSMEs: A Qualitative Study of Environmental Awareness, Recording, and Cost Management - Anisatun Humayrah Rais (Universitas Negeri Makassar, 2026)
This study aims to examine environmental accounting practices in micro, small, and medium enterprises (MSMEs) in the printing industry, focusing on business awareness, cost recording, and environmental cost and waste management. This study uses a qualitative approach with a case study design involving several MSMEs in the printing industry that provide photocopying, document printing, binding, lamination, scanning, photo printing, and stationery sales services. Data were collected through semi-structured interviews with owners, production employees, cashiers, and sales staff, supported by observations and documentation of daily operational activities. Data were analyzed thematically by identifying recurring patterns related to environmental awareness, cost recognition, waste management, resource efficiency, and barriers to recording environmental costs. The findings indicate that environmental accounting in MSMEs in the printing industry has not been formally implemented through specific accounts, reports, or structured recording systems. Costs related to paper, ink, toner, electricity, laminated plastic, machine maintenance, and waste are still recorded as general operational costs. However, environmental accounting practices appear informal, including efforts to reduce printing errors, reuse single-sided paper, offer double-sided printing, collect waste paper, manage used cartridges or toner cartridges, and turn off unused equipment. This study shows that cost efficiency is a key entry point for introducing green accounting in printing MSMEs. A simple format for recording environmental costs is needed to help businesses identify material use, waste, and hidden environmental costs without adding excessive administrative burden.